Efektivitas Model Problem Based Learning dan Picture and Picture Menggunakan Media Google Earth Web terhadap Kemampuan Berpikir Spasial Peserta Didik Kelas XI SMA Al Islam 1 Surakarta - Khalidya Anindra Pertiwi; Sugiyanto Sugiyanto; Lintang Ronggowulan (GEADIDAKTIKA, 2025)
This study examines the effectiveness of the Problem-Based Learning (PBL) and Picture and Picture (PnP) models using Google Earth Web media in improving the spatial thinking skills of 11th-grade students at SMA Al Islam 1 Surakarta on the topic of the distribution of flora and fauna in Indonesia. The research aims to determine differences in spatial thinking abilities between students taught using the PBL model and those taught using the PnP model, as well as to identify which model is more effective when integrated with Google Earth Web. This quasi-experimental study employs a pretest–posttest control group design with simple random sampling. Data were analyzed using prerequisite tests, the Mann–Whitney test, and the N-Gain Score to measure effectiveness levels. The results show that students taught with the PBL model experienced an increase of 25.09 points in spatial thinking skillswhile those taught with the PnP model increased by 20.55 points. The Mann–Whitney test yielded an Asymp. Sig. (2-tailed) value of 0.000 < 0.05, indicating that PBL with Google Earth Web is significantly more effective. The N-Gain Score for the PBL class (XI 6) was 65.20%, categorized as quite effective, while the PnP class (XI 7) achieved 53.94%, indicating lower effectiveness.